Comparison of thein vitroactivity of ampicillin and moxifloxacin againstListeria monocytogenesat achievable concentrations in the central nervous system. Issue 6 (June 2017) - Pupo, Inmaculada; Lepe, Jose A.; Smani, Younes; Aznar, Javier
Abstract : Purpose. : The aim of this study was to compare the in vitro activity of ampicillin and moxifloxacin against six isolates selected from 154 invasive clinical isolates of Listeria monocytogenes and evaluate their intra‐ and extracellular activities with achievable central nervous system concentrations obtained using Monte Carlo simulations with conventional and unconventional dosages. Methodology. : The MICs and minimal bactericidal concentrations (MBCs) of ampicillin and moxifloxacin were determined by using the broth microdilution method. The intra‐ and extracellular activities were compared using time‐kill curves and inhibition of intracellular growth assays. Results. : The MICs50/90 of ampicillin were 0.125/0.5 mg l −1 and the MBC50/90 was ≥16 mg l −1, while the moxifloxacin MICs50/90 were 0.25/0.5 mg l −1 and the MBC50/90 was 0.5 mg l −1 . Ampicillin did not show any extracellular bactericidal activity at 24 h, although bactericidal activity was detected at 48 h. For moxifloxacin, the bactericidal effect was evident after 6 h of incubation. Both antibiotics achieved significant reductions in intracellular inoculum after 1‐24 h of incubation; however, moxifloxacin becomes bactericidal more rapidly, producing a much greater reduction in the inoculum in the first hour than ampicillin. There were no differences among the MIC and MBC values of moxifloxacin and ampicillin among the strains belonging to different serotypes and/or epidemic clones. This fact was also found in the intra‐ and extracellular studies. Conclusion. : The results of this study demonstrated the faster bactericidal activity of moxifloxacin at achievable central nervous system concentrations against intra‐ and extracellular forms of L. monocytogenes in comparison with ampicillin.